Self-assemblies of nucleolipid supramolecular synthons show unique self-sorting and cooperative assembling process - Nuthanakanti, Ashok; Walunj, Manisha B.; Torris, Arun; Badiger, Manohar V.; Srivatsan, Seergazhi G. (Nanoscale, 2019)
The inherent control of the self-sorting and co-assembling process that has evolved in multi-component biological systems is not easy to emulate in vitro using synthetic supramolecular synthons. Here, using the basic component of nucleic acids and lipids, we describe a simple platform to build hierarchical assemblies of two component systems, which show an interesting self-sorting and co-assembling behavior. The assembling systems are made of a combination of amphiphilic purine and pyrimidine ribonucleoside-fatty acid conjugates (nucleolipids), which were prepared by coupling fatty acid acyl chains of different lengths at the 2 `-O- and 3 `-O-positions of the ribose sugar. Individually, the purine and pyrimidine nucleolipids adopt a distinct morphology, which either supports or does not support the gelation process. Interestingly, due to the subtle difference in the order of formation and stability of individual assemblies, different mixtures of supramolecular synthons and complementary ribonucleosides exhibit a cooperative and disruptive self-sorting and co-assembling behavior. A systematic morphological analysis combined with single crystal X-ray crystallography, powder X-ray diffraction (PXRD), NMR, CD, rheological and 3D X-ray microtomography studies provided insights into the mechanism of the self-sorting and co-assembling process. Taken together, this approach has enabled the construction of assemblies with unique higher ordered architectures and gels with remarkably enhanced mechanical strength that cannot be derived from the respective single component systems.

Sulfonated polyvinyl alcohol ionomer membrane favoring smooth electrodeposition of zinc for aqueous rechargeable zinc metal batteries - Vijayakumar, Vidyanand; Torris, Arun; Kurian, Maria; Mathew, Megha Mary; Ghosh, Meena; Khairnar, Ajay B.; Badiger, Manohar V.; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2021)
One of the failure mechanisms of aqueous rechargeable zinc metal batteries (AZMBs) involves high surface area zinc (HSAZ)/dendrite-like deposits over the Zn-metal anode during long-term cycling. Negatively charged (anionic) polymeric ionomer electrolyte membranes and separators are known for suppressing the dendrite-/HSAZ-induced failure of AZMBs. However, the preparation of cost-effective and non-fluorinated ionomers from cheap and environmentally friendly polymers is essential to leverage the feasibility of AZMBs. The current work demonstrates the potential of an ionomer electrolyte membrane (P-AS-C-Zn) made by the crystallization-induced physical cross-linking of sulfonated poly (vinyl alcohol) (PVS) and poly (vinyl alcohol) (PVA) as a dendrite-/HSAZ-inhibiting separator for AZMBs. The P-AS-C-Zn membranes exhibited excellent Zn plating/stripping behavior with a stable voltage vs. time profile beyond 1100 h, compared to their neutral PVA-C-Zn counterpart without any ionomer character (cell failure at close to 280 h). Applying the optimized P-AS-C-Zn membrane in a MnO2||Zn full cell helps retain about 50% of the initial capacity close to 600 cycles in the absence of extra manganese salt in the electrolyte, which is indeed promising.

Study on anisotropy in wire arc additively manufactured Inconel 625 multi-layered wall and its correlation with molten pool thermal history - Nagallapati, Vishwanath; Choudhary, Amit; Torris, Arun; Muvvala, Gopinath; Dadasaheb, Sagar Pawar; Gudur, Srinath Ellaswamy (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
In the present study, the variation in molten pool thermal history with layer number during wire arc additive manufacturing of Inconel 625 wall was investigated. Further, its effect on the evolution of microstructure and anisotropy in mechanical and corrosion properties was reported. During the deposition process, the molten pool thermal history was monitored using a non-contact type IR pyrometer operating at 1.6 mu m wavelength. A total number of 40 layers were deposited, building a wall of 60 mm height. With an increase in layer number, the molten pool lifetime and cooling rate were found to increase and decrease, respectively, resulting in coarse grains and increased elemental segregation or Laves phase formation. To investigate its effect on mechanical properties, the samples were collected in a skewed fashion along the height with orientation in the deposition direction. The tensile specimens collected close to the substrate exhibited better strength and ductility, while the samples from the top location of the wall exhibited a relatively brittle mode of fracture, which was investigated by carrying out the fracture surface analysis using SEM. Corrosion test was also conducted along the height of the wall, wherein the samples close to substrate exhibited better corrosion resistance due to refined microstructure and low elemental segregations. Further, EDS, XRD analysis and hardness test were carried out to investigate the elemental composition, variation in phases and hardness with layer number, respectively.
Keywords: anisotropy; Layer number; mechanical properties; Molten pool thermal history; Wire arc additive manufacturing

Synthesis and characterization of partially biobased aromatic (Co)polycarbonates containing biphenylene units and pendant pentadecyl chains - Ichake, Amol B.; Nagane, Samadhan S.; Jadhav, Uday A.; Torris, Arun; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (Macromolecular Chemistry and Physics, 2022)
2-Pentadecyl-[1,1''-biphenyl]-4,4''-diol (PBD) is synthesized starting from cashew nut shell liquid-a by-product of cashew processing industry. A new series of partially biobased aromatic (co)polycarbonates possessing biphenylene units and pendant pentadecyl chains is synthesized by solution polycondensation of PBD or varying compositions of PBD and bisphenol-A with triphosgene in dry dichloromethane. Inherent viscosities and number average molecular weights of (co)polycarbonates are in the range 0.51-1.24 dL g(-1) and 18 x 10(3)- 43.4 x 10(3) g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. Flexible, transparent, and free-standing films of (co)polycarbonates can be cast from chloroform solution. (Co)polycarbonates are characterized using Fourier transform infrared spectroscopy (FTIR), H-1 NMR, C-13 NMR spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry, and thermogravimetric analysis. T-10 and T-g values of (co)polycarbonates are in the range 417-433 and 8-147 degrees C, respectively. It is demonstrated that the T-g values can be tuned by incorporation of appropriate mol% of PBD as a comonomer in Bisphenol-A-based copolycarbonates. The lowering of the T-g values of (co)polycarbonates can be attributed primarily to the packing disruptive effect of flexible pentadecyl chains. Furthermore, the effect of incorporation of PBD as a comonomer on water contact angle values of (co)polycarbonates is evaluated.
Keywords: aromatic polycarbonates; biobased bisphenol; Cashew nut shell liquid; pentadecyl chain; Renewable resources

Self-healing hydrogel electrolyte enabled by dynamic polar covalent and noncovalent interactions for high-performance rechargeable zinc-metal batteries: a leap toward sustainable energy storage - Puthiyaveetil, Priyanka Pandinhare; Kurian, Rachna Maria; Samudre, Nikhil S.; Balasubramanian, Rajalakshmi; Torris, Arun; Pockil, Fayis Kanheeram; Bhat, Suresh; Ajithkumar, T. G.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Advanced Energy Materials, 2026)
Hydrogel polymer electrolytes with superior multifunctional properties are promising alternatives to aqueous electrolytes for resolving interfacial issues in rechargeable zinc-metal batteries. In this study, an intrinsic self-healing hydrogel polymer electrolyte (PHBC-4) is synthesized, engineered through an integrated approach involving the polar covalent (B & horbar;O bond), hydrogen-bond (polyvinyl alcohol-hydroxypropyl methylcellulose interface), and coordination-type (Zn & horbar;O) interactions to enable self-healing functionality. The PHBC-4 has demonstrated high ionic conductivity (4.6 x 10-2 S cm-1), good oxidative stability (2.3 V vs Zn|Zn2+), a high cation transference number (0.89), superior tensile strength (0.32 MPa), and an impressive healing efficiency of 93% achieved just within 5 min, confirming its robust self-healing capability. In Zn||Zn symmetric cells, it effectively suppresses dendrite growth, ensuring stable cycling for over 1032 h with an areal capacity of 1.0 mAh cm-2 at a current density of 1.0 mA cm-2. When paired with a Zn-doped MnO cathode in the rechargeable homemade pouch cell, the system delivers a high specific capacity of 160 mAh g-1 at 0.10 A g-1 and cycling stability up to 493 charge-discharge cycles at 2.0 A g-1. The self-healing ability of PHBC-4 HGPE is confirmed in a homemade pouch cell via OCV and charge-discharge tests, demonstrating stable performance. The DFT studies confirm molecular-level interactions within the hydrogel heterostructure.
Keywords: dendrite inhibition; flexible rechargeable zinc metal battery; high cation transference number; self-healing hydrogel polymer electrolyte